Tinjauan Terhadap Penerapan Sistem Automasi di Perpustakaan Politeknik Pertanian Universitas Andalas Payakumbuh - Sari, Nurniati; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This study aimed to describe: (1) automation system working procedure in mengautomasikan Politani Library activities, (2) the policy provided by the library to automate the activities especially in pengentrian Library Politani data, and (3) human resources contained in Library Politani. Data were collected through observation and interviews with staff and former chairman Politani Library. Analyzing the data be descriptive. Based on observations and interviews obtained the following findings. (1) the implementation of work procedures in the library automation system Politani enough, from the preparation to the use of automation systems. It's just not a consideration of the completeness of the hardware and human resource capabilities in the preparation process. The lack of consideration of the distance to the survey process. (2) Policy to automate activities in the library is still lacking because Politani automate policy activities at the library as just training. Politani library also requires the addition of a complete infrastructure and facilities in the development of automation systems, automation system development in order to function optimally. (3) The ability of the human resources Politani library is still limited in terms of library automation. This is due to the lack of human resources library master the basics of computer hardware and software. In addition, the lack of knowledge about the information technology staff, making it difficult to develop automation.